Producing high quality RDF to enhance waste-to-energy plants efficiency - Lam, Wan Yee. (2012)
The project involves the production of a high quality Refuse Derived Fuel (RDF) from municipal solid waste to maximise energy efficiency and minimise environmental impact. An experimental study was undertaken to examine the physiochemical properties and heating values of common waste types in Singapore.